2017
DOI: 10.1101/214460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divalent metal cations potentiate the predatory capacity of amoeba forCryptococcus neoformans

Abstract: 19Among the best studied interaction between soil phagocytic predators and a human pathogenic fungus 20 is that of Acanthamoeba castellanii and Cryptococcus neoformans. The experimental conditions used in 21 amoeba-fungal confrontation assays can have major effects on whether the fungus or the protozoan is 22 ascendant in the interaction. . Cations enhanced A. castellanii activity against C. 29 neoformans through enhanced phagocytosis, which is the major mechanism for amoeba to kill fungal 30 cells. We found n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…However, our results are in accordance with previously published studies of fungal-amoeba interactions, in which A. castellanii was shown to efficiently use C. neoformans as a food source and was considered an important factor controlling fungi in the environment [35, 36]. More recently, Fu and Casadevall reported that divalent cations have the ability to increase amoeba survival and potentiate their fungal killing abilities [37]. Their work points to one of the factors that might influence the outcome of fungal-amoeba interaction assays.…”
Section: Discussionsupporting
confidence: 92%
“…However, our results are in accordance with previously published studies of fungal-amoeba interactions, in which A. castellanii was shown to efficiently use C. neoformans as a food source and was considered an important factor controlling fungi in the environment [35, 36]. More recently, Fu and Casadevall reported that divalent cations have the ability to increase amoeba survival and potentiate their fungal killing abilities [37]. Their work points to one of the factors that might influence the outcome of fungal-amoeba interaction assays.…”
Section: Discussionsupporting
confidence: 92%
“…Fungal viability within Ac was compared with viability in axenic culture medium alone. PYG was elected as the medium for the best growth of amoeba during the interactions, and the presence of divalent cations has shown to potentiate the predatory capacity of Ac (Fu & Casadevall, ). Upon interaction with Ac for 2 hr and washes, interacting fungi viability was followed for 48 hr.…”
Section: Resultsmentioning
confidence: 99%
“…Whether these interactions reflect actual prey–predator relationships between fungi and amoebae is currently not known, as even for A. castellanii killing of Cr. neoformans was found to vary depending on the experimental conditions (Fu and Casadevall, ). Mycophagy is well documented for several species across the Amoebozoa and eponymous for Protostelium mycophaga , the first isolated species from the genus Protostelium (Olive and Stoianovitch, ).…”
Section: Introductionmentioning
confidence: 99%